Ethnobotany of Plants as Handicrafts by The Dayak Kerambay Tribe Community in Raut Muara Village - Tiara Putri Rahmatika; Syamswisna Syamswisna; Asriah Nurdini Mardiyyaningsih (Jurnal Biologi Tropis, 2023)
Ethnobotany is a depiction of the use of natural plants by local people for various activities such as rituals, handicrafts, food, cosmetics, and medicinal materials. The Dayak Kerambay etnic still uses many plants as handicraft materials. This study aims to determine the types of plants that can be used as handicrafts by the people of Raut Muara Village, Sanggau Regency from the results of ethnobotany. The collection of ethnobotanical results was carried out by triangulation techniques, namely semi-structured interviews, documentation of handicraft plants and observation to the field. From the results of this study, 29 types and 11 families of plants were obtained that have the potential to be handicraft plants and are widely used by the Kerambay dayak tribe community in Raut Muara Village for generations. There are 10 types of rattan plants that are often used by the people of the Kerambay dayak tribe for the needs of life and work activities with the products produced, namely bubu (Ju), takin, penampi', bakul, keranjang and ayakan. The potential use of rattan as a source of income because it has high economic value, such as being used household furniture and completeness of work activities.